Role of Railway Transportation in the Spread of the Coronavirus: Evidence From Wuhan-Beijing Railway Corridor - Liu, Rucheng; Li, Dan; Kaewunruen, Sakdirat (Frontiers in Built Environment, 2020)
The last several months have marked a notable surge in a pandemic called coronavirus. The disease has infected ten million people all around the world and has gained a notable attention in the field of research. Allegedly originated in China, the virus has spread to nearly every country across the globe. The current study aims to analyse the spread of coronavirus potentially through rail transport by considering the case of Wuhan-Beijing railway corridor in China. This study adopts a quantitative methodology to analyse the spread of the disease due to an immense travelling of people through Wuhan-Beijing railway line. By analysing the primary data through statistical technique, this study proposes new practical recommendations enabling sustainable urban environment and improving societal resilience, in the face of the massive outbreak of coronavirus in Wuhan.